2013
DOI: 10.1159/000345954
|View full text |Cite
|
Sign up to set email alerts
|

Oral Challenges with Four Apple Cultivars Result in Significant Differences in Oral Allergy Symptoms

Abstract: Background: We analyzed the hypoallergenic potential of a recently bred apple selection with unusually low content of Mal d 1, using an oral challenge model with three additional apple cultivars for comparison. Methods: Sixty-six birch pollen-allergic individuals with a history of oral allergy syndrome after apple intake were subjected to a double-blind oral provocation with two apple cultivars (B:0654 and ‘Discovery'). Thirteen also tested two other apple cultivars (‘Ingrid Marie' and ‘Gloster'). Three doses … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 19 publications
(36 reference statements)
0
10
0
1
Order By: Relevance
“…A break of at least 2 days was induced between each challenge. OPT has been modified after Nybom et al 25 and Kopac et al, 7 so increasing amounts of allergenic apple pieces were given to patients to consume (Fig. 1).…”
Section: Oral Provocationsmentioning
confidence: 99%
“…A break of at least 2 days was induced between each challenge. OPT has been modified after Nybom et al 25 and Kopac et al, 7 so increasing amounts of allergenic apple pieces were given to patients to consume (Fig. 1).…”
Section: Oral Provocationsmentioning
confidence: 99%
“… 2 3 4 5 6 7 8 According to recent reports, up to 90% of patients allergic to birch pollen Bet v 1 or its homologues show immunoglobulin E (IgE)-mediated reactions to plant fruits including apples. 9 10 11 An increasing number of reports have demonstrated Bet v 1-specific T lymphocyte reactions with related food homologues. 2 3 12 13 Jahn-Schmid and colleagues 3 showed that T lymphocytes specific for the Bet v 1 142-156 epitope were triggered to produce cytokines and proliferate in response to homologous pathogenesis-related (PR)-10-like allergens such as Api g 1, Cor a 1, Dau c 1, Gly m 4, Pru av 1, and Mal d 1.…”
Section: Introductionmentioning
confidence: 99%
“…Although Santana, Topaz, Pink Lady, and Elise were all classified as low allergenic [ 28 , 30 ], VAS scores of Santana were significantly lower than those of Topaz and VAS scores of Elise were significantly lower than those of Santana and Pink Lady [ 29 , 30 ]. Neither SPT nor Mal d 1 content seem to predict allergenicity of different apple cultivars as determined by food challenge [ 40 ].…”
Section: Discussionmentioning
confidence: 99%